1989
DOI: 10.1051/parasite/1989643200
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania (Viannia) shawisp. n., a parasite of monkeys, sloths and procyonids in Amazonian brazil

Abstract: SUMMARY. Leishmania (Viannia) shawi sp. n., is described from the monkeys Cebus apella and Chiropotes satanus, the sloths Choloepus didactylus and Bradypus tridactylus, the procyonid Nasua nasua, and the phlebotomine sandfly Lutzomyia whitmani, all from primary forest in the State of Par, north Brazil. L. (V.) shawi is variably distinguished from all other known species within the subgenus Viannia by a combination of biological, biochemical and serological cha racters, as revealed by studies on morphology, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
5

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 6 publications
0
42
0
5
Order By: Relevance
“…Diferentemente das outras áreas endêmicas do Estado do Rio de Janeiro, a Lutzomyia whitmani foi à segunda espécie mais freqüente, substituindo a Lutzomyia migonei que comumente precede a Lutzomyia intermedia como a segunda espécie mais freqüente nas áreas endêmicas de LTA 6 . Apesar da baixa densidade de Lutzomyia whitmani, é importante observar que esta espécie é tida como o principal vetor de Leishmania (Viannia) braziliensis em diversas regiões do país 16 20 e associado à transmissão de Leishmania (Viannia) guyanensis e Leishmania (Viannia) shawi 13 .…”
Section: Discussionunclassified
“…Diferentemente das outras áreas endêmicas do Estado do Rio de Janeiro, a Lutzomyia whitmani foi à segunda espécie mais freqüente, substituindo a Lutzomyia migonei que comumente precede a Lutzomyia intermedia como a segunda espécie mais freqüente nas áreas endêmicas de LTA 6 . Apesar da baixa densidade de Lutzomyia whitmani, é importante observar que esta espécie é tida como o principal vetor de Leishmania (Viannia) braziliensis em diversas regiões do país 16 20 e associado à transmissão de Leishmania (Viannia) guyanensis e Leishmania (Viannia) shawi 13 .…”
Section: Discussionunclassified
“…Since Leishmania infection and/or presence of anti-Leishmania antibodies had been already reported in Cerdocyon thous (8,9,20), Lycalopex vetulus (9,20), Cebus apella (11) and Nasua nasua (11), these animals were pinpointed as Leishmania (40) detected parasites of the Leishmania genus in this species.…”
Section: Search For Antibodies By Datmentioning
confidence: 99%
“…Whereas Leishmania (Leishmania) chagasi has been isolated from crab-eating foxes (Cerdocyon thous), Leishmania (Viannia) lainsoni was found in pacas (Agouti paca) (8)(9)(10). Leishmania (Viannia) shawi, in turn, has been detected in capuchin monkeys (Cebus apella), bearded sakis (Chiropotes satanas), coatis (Nasua nasua) (11), three-toed sloths (Bradypus tridactylus) and two-toed sloths (Choloepus didactylus) (11). Leishmania (L.) mexicana has been found in big-eared climbing rats (Ototylomys phyllotis), blackeared rice-rats (Oryzomys melanotis), Yucatan deer-mice (Peromyscus yucatanicus) and hispid cotton rats (Sigmodon hispidus) (12).…”
Section: Introductionmentioning
confidence: 99%
“…
Leishmania (Viannia) shawi Lainson, Braga, de Souza, Póvoa, Ishikawa & Silveira, 1989, was originally recorded from monkeys (Cebus apella and Chiropotes satanas), sloths (Choloepus didactylus and Bradypus tridactylus) and coatis (Nasua nasua) and the sandfly, Lutzomyia whitmani. With a panel of Leishmania specific mono clonal antibodies, it was found that 30.5 % of the Leishmania strains from patients, who had contracted cutaneous leishmaniasis in Para State, were similar, but not identical to L. (V.) guyanensis.

The enzyme profiles of 18 of these strains were determined, and it was found that 12 isolates belonged to the same zymodeme as the type strain of L.

…”
mentioning
confidence: 99%